Contactless monitoring of respiratory rate (RR) and heart rate (HR) in non-acuity settings: a clinical validity study - Muralidhar Varma; Manikanda Krishnan Vaidyanathan; Joseph Thomas; Trevor Sequeira; Navaneetha Krishnan S Naidu; Yogish Mallya; Amarendranath Sunkara; Praveen Patil; Nagaraj Poojary; Benoît Balmaekers; Shankar Prasad N; Sulochana Badagabettu (BMJ Open, 2022)
Objective Patient monitoring in general wards primarily involves intermittent observation of temperature, heart rate (HR), respiratory rate (RR) and blood pressure performed by the nursing staff. Several hours can lapse between such measurements, and the patient may go unobserved. Despite the growing widespread use of sensors to monitor vital signs and physical activities of healthy individuals, most acutely ill hospitalised patients remain unmonitored, leaving them at an increased risk. We investigated whether a contactless monitoring system could measure vital parameters, such as HR and RR, in a real-world hospital setting.Design A cross-sectional prospective study.Setting and participants We examined the suitability of employing a non-contact monitoring system in a low-acuity setup at a tertiary care hospital in India. Measurements were performed on 158 subjects, with data acquired through contactless monitoring from the general ward and dialysis unit.Outcome measures Vital parameters (RR and HR) were measured using a video camera in a non-acuity setting.Results Three distinct combinations of contactless monitoring afforded excellent accuracy. Contactless RR monitoring was linearly correlated with Alice NightOne and manual counts, presenting coefficients of determination of 0.88 and 0.90, respectively. Contactless HR monitoring presented a coefficient of determination of 0.91. The mean absolute errors were 0.84 and 2.15 beats per minute for RR and HR, respectively.Conclusions Compared with existing Food and Drug Administration-approved monitors, the findings of the present study revealed that contactless monitoring of RR and HR accurately represented study populations in non-acuity settings. Contactless video monitoring is an unobtrusive and dependable method for monitoring and recording RR and HR. Further research is needed to validate its dependability and utility in other settings, including acute care.Trial registration number CTRI/2018/11/016246.